CROSSCULTURAL UNDERSTANDING STRATEGY IN SPEAKING LESSON TO OVERCOMING SPEAKING ANXIETY - Anggraeni, Anita; Rachmijati, Cynantia (Research And Innovation In Language Learning (RILL), 2018)
The students are generally inseparable from liking popular culture to become a fan Â and finally become their identity. In addition to favoring Western culture, there have also been other great cultures lately, for example Japanese, Korea, Thailand and so on. This study aims to examine whether with cross cultural knowledge students are expected to be more confident in speaking and reducing talking anxiety. This research method is descriptive qualitative research method. The data in this study were obtained from interviews and questionnaires adapted from Horwitzs "Language Classroom Anxiety Scale (FLCAS)" and Oregon Universitys "Value Rubric Intercultural Knowledge". It was found that the cause of speaking anxiety was 79% internal factor, 85% lack of knowledge and 30% faculty and friend factor. The result of the research found that the correlation between cultural understanding is closely related to the decreasing of students anxiety level in speaking english. It can be concluded that CCU does help in overcoming students speaking anxiety.Keywords :cross cultural understanding, speaking, anxiety